Rural schools of Bizkaia (1920-1937). Review and new data - Artetxe Sanchez, Karmele (Historia y Memoria de la Educación, 2020)
The objective of this article is to review the existing historiography on the Escuelas de Barriada (Rural Schools of Bizkaia Province, Basque Country), created and promoted by the Provincial Council of Bizkaia between 1920-1937, giving nuance to certain issues and providing new data on four aspects. The first of these is the question of instructional language. The use of Basque in the classroom was progressively reduced in favor of Spanish almost from the first moment and did not provoke opposition from teachers, even though many of them were Basque nationalists. Secondly, we provide an analysis of the initial curriculum, which presented a more pedagogical rather than ideological approach, oriented towards a teaching style that was more comprehensive than memory-based. This was especially appreciable in the areas of mathematics and geometry, where exclusionary political indoctrination was avoided, with content referring to both Basque and Spanish identity. Thirdly, we analyse the alleged use of books containing Basque nationalist political content in these schools, of which we have found no evidence. And finally, we offer an overview of the type of teachers that worked in these schools, including an analysis of their ideological profile: more than 90% of the faculty was composed of women, generally young, single, Basque-speaking, Catholic and ideologically sympathetic to Basque nationalism . The research focuses on the 1920-1930 period, when the Provincial Council of Bizkaia was governed by Monarchists and when the Dictatorship of Primo de Rivera began. This was the period when the original pro-Basque project of these schools was transformed. Some data and questions about the later era are also presented.